Pengaruh Pemberian Informasi tentang Asuhan Perkembangan pada BBLR terhadap Tingkat Pengetahuan dan Sikap Perawat di Rumah Sakit Al Islam Bandung - Yusi Sofiyah (The Journal General Health and Pharmaceutical Sciences Research, 2024)
Development care is an effort to modify the environment and respond to changes in the behavior of newborns, especially in infants Low Birth Weight, The purpose of this study was to determine the effect of training on developmental care on nurses' ability to care for babies with low birth weight. The design of this study used "quasi experiment pre and post test control", which involved 19 nurses in the perinatology room of Al Islam Bandung Hospital. The results showed a significant increase in the mean score of nurses' knowledge, attitudes and actions after the intervention (p value = 0,000, α = 0.05). This training is effective in increasing nurses' knowledge and attitudes. The recommendation of this study is the need for socialization to all health workers supported by the hospital policy to implement development care and evaluate the implementation of development care in LBW care.